CTLs From Patients With Atherosclerosis Show Elevated Adhesiveness and Distinct Integrin Expression Patterns on 2D Substrates - Potashnikova, Daria M.; Saidova, Aleena A.; Tvorogova, Anna V.; Anisimova, Alexandra S.; Botsina, Alexandra Yu; Vasilieva, Elena Yu; Margolis, Leonid B. (Frontiers in Medicine, 2022)
Atherosclerosis is the major cause of cardiovascular disease that is characterized by plaque formation in the blood vessel wall. Atherosclerotic plaques represent sites of chronic inflammation with diverse cell content that is shifted towards the prevalence of cytotoxic T-lymphocytes (CTLs) upon plaque progression. The studies of CTL recruitment to atherosclerotic plaques require adequate in vitro models accounting for CTL interactions with chemokine-ligands and extracellular matrix fibers via surface chemokine receptors and integrins. Here we applied such model by investigating CTL adhesion and migration on six types of coated surfaces. We assessed adhesion and motility metrics, the expression of chemokine receptors and integrins in CTLs of patients with atherosclerosis and healthy donors. Using fibronectin, platelet-poor plasma from patients with atherosclerosis and conditioned medium from atherosclerotic plaques we revealed the role of substrate in CTL adhesiveness: fibronectin alone and fibronectin combined with platelet-poor plasma and conditioned medium elevated the CTL adhesiveness – in patients the elevation was significantly higher than in healthy donors (p=0.02, mixed 2-way ANOVA model). This was in line with our finding that the expression levels of integrin-coding mRNAs were elevated in the presence of fibronectin (p<0.05) and ITGB1, ITGA1, ITGA4 were specifically upregulated in patients compared to healthy donors (p<0.01). Our experimental model did not affect the expression levels of mRNAs CCR4, CCR5, CX3CR1 coding the chemokine receptors that drive T-lymphocyte migration to plaques. Thus we demonstrated the substrate-dependence of integrin expression and discriminated CTLs from patients and healthy donors by adhesion parameters and integrin expression levels.